2007
DOI: 10.1111/j.1471-8286.2007.01817.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of microsatellite markers in Dendrobium officinale, an endangered herb endemic to China

Abstract: As an invaluable herb, Dendrobium officinale has been in severe danger since 1950 because of human exploitation and habitat deterioration. In order to investigate the genetic diversity and structure of this species, we isolated and characterized 12 microsatellite loci derived from two microsatellite-enriched libraries. Twenty-two individuals from Leye population were analysed. These loci were polymorphic and displayed three to 12 alleles per locus. The observed and expected heterozygosities ranged from 0.150 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 8 publications
0
11
0
2
Order By: Relevance
“…The mean expected heterozygosity across loci within populations of D. thyrsiflorum ranged from 0.76 to 0.82, suggesting that this species has a high level of genetic diversity comparable to that of other Dendrobium species. 10,33,34) Based on a published study, 12) a high level of genetic diversity of D. thyrsiflorum may increase the power of the statistical analysis for identifying the origin of living or processed D. thyrsiflorum samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean expected heterozygosity across loci within populations of D. thyrsiflorum ranged from 0.76 to 0.82, suggesting that this species has a high level of genetic diversity comparable to that of other Dendrobium species. 10,33,34) Based on a published study, 12) a high level of genetic diversity of D. thyrsiflorum may increase the power of the statistical analysis for identifying the origin of living or processed D. thyrsiflorum samples.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous lines of evidence have demonstrated that SSRs exist in any region of eukaryotic genomes, including coding and non-coding regions. Microsatellite markers have been used to identify the geographic origins of commercially available herbs 10) and shown to be an effective tool for individual assignment [11][12][13][14][15] as well as genetic variation analysis for various species 16,17) due to their features: composite genotypes across several loci, relatively high polymorphism, and co-dominant inheritance. 15,18) On the other side, microsatellite markers are quite species-specific, which limits their use as a universal tool for testing multiple species.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…The primers were used to amplify SSR loci in D. nobile genomic DNA, and the amplified bands with bands that were clear and the expected size were sequenced to validate the corresponding repeat motifs. All of the sequences of the developed D. nobile SSRs were compared with the Dendrobium SSRs that were previously reported (Gu et al, 2007;Xie et al, 2010;Lu et al, 2012Lu et al, , 2013 in order to determine that they were novel.…”
Section: Isolation Of Est-ssrs Primer Design and Marker Validationmentioning
confidence: 99%
“…However, as a non-model plant that lacks a sequenced genome, thus far only over a hundred Dendrobium simple sequence repeat (SSR) markers have been reported (Gu et al, 2007;Xie et al, 2010;Lu et al, 2012a,b). Here, we present the development of novel polymorphic expressed sequence tag (EST)-SSRs in D. nobile, which will be helpful for potential genetic applications.…”
Section: Introductionmentioning
confidence: 99%